Organic Farming – A Gateway for better living - Neeraja, C R; Anjana, R S (Indian Farming, 2017)
With the increase in population, our compulsion would be not only to stabilize agricultural production but to increase it further in a sustainable manner. The scientists have realized that the ‘Green Revolution’ with high input use has reached a plateau and isnow sustained with diminishing return of falling dividends. Thus, anatural balance needs to be maintained at all cost for theexistence of life and property. Organic farming envisages a comprehensive management approach to improve soil health, the ecosystem of the region and quality of produce. It benefits society substantially by reducing pollution; conserving energy, soil, nutrients, fish, and wildlife; and assuring the supply of safe and healthy food for future generations.